2017
DOI: 10.1302/2046-3758.67.bjr-2016-0342.r1
|View full text |Cite
|
Sign up to set email alerts
|

Re-using blood products as an alternative supplement in the optimisation of clinical-grade adipose-derived mesenchymal stem cell culture

Abstract: ObjectivesAdipose-derived mesenchymal stem cells (ADMSCs) are a promising strategy for orthopaedic applications, particularly in bone repair. Ex vivo expansion of ADMSCs is required to obtain sufficient cell numbers. Xenogenic supplements should be avoided in order to minimise the risk of infections and immunological reactions. Human platelet lysate and human plasma may be an excellent material source for ADMSC expansion. In the present study, use of blood products after their recommended transfusion date to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In the vast majority of reports the ability of hMSCs to be differentiated along pre-determined lineages was not affected by being cultured using hPL: adipogenic, osteogenic and chondrogenic differentiation were demonstrated with no relevant difference in effectiveness or potential to the same hMSCs cultured with FBS. In three cases MSCs, expanded in hPL, were more effectively differentiated along osteogenic, chondrogenic and adipogenic routes [ 37 , 49 , 58 ]; others reported a difference only for osteogenic [ 17 , 40 , 42 , 47 , 54 ] or adipogenic differentiation respectively [ 19 , 31 ]. Only one publication reported that FBS supported osteogenic and adipogenic differentiation to a higher degree [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the vast majority of reports the ability of hMSCs to be differentiated along pre-determined lineages was not affected by being cultured using hPL: adipogenic, osteogenic and chondrogenic differentiation were demonstrated with no relevant difference in effectiveness or potential to the same hMSCs cultured with FBS. In three cases MSCs, expanded in hPL, were more effectively differentiated along osteogenic, chondrogenic and adipogenic routes [ 37 , 49 , 58 ]; others reported a difference only for osteogenic [ 17 , 40 , 42 , 47 , 54 ] or adipogenic differentiation respectively [ 19 , 31 ]. Only one publication reported that FBS supported osteogenic and adipogenic differentiation to a higher degree [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, human serum enhances the ASCs proliferation without any differences in morphology or immunostaining profile compared to traditional culture with FBS [53]. Blood-derived products consisted of many growth factors compared to FBS or FCS can be useful to maintain the high proliferation rate, stem cell properties, and differentiation characteristics of ASCs in long-term cultivation [53,56]. Moreover, the combination of platelet lysate and human plasma which are isolated from expired blood can reduce senescence of ASCs during cultivation [56].…”
Section: Processes In the Culture Of Ascsmentioning
confidence: 99%
“…Blood-derived products consisted of many growth factors compared to FBS or FCS can be useful to maintain the high proliferation rate, stem cell properties, and differentiation characteristics of ASCs in long-term cultivation [53,56]. Moreover, the combination of platelet lysate and human plasma which are isolated from expired blood can reduce senescence of ASCs during cultivation [56]. Besides, platelet-rich plasma added medium can stimulate the differentiation of ASCs into chondroblasts [57].…”
Section: Processes In the Culture Of Ascsmentioning
confidence: 99%
“…Preclinical data indicate that blood-derived products support the maintenance of cell proliferation, as well as stem cell properties and differentiation characteristics in in vitro settings [26,27]. Moreover, a combination of platelet lysate and human plasma may reduce senescence of AD-MSCs in culture [27]. PRP-enriched medium specifically was shown to enhance chondrogenic differentiation of AD-MSCs [28].…”
Section: Introductionmentioning
confidence: 99%